2012
DOI: 10.1590/s2176-94512012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the mandibular symphysis of Caucasian Brazilian adults with well-balanced faces and normal occlusion: the influence of gender and facial type

Abstract: OBJECTIVE: This study aimed to establish cephalometric reference values for mandibular symphysis in adults. Dentoalveolar, skeletal and soft tissue variables were measured considering the influence of gender and facial type. METHODS: The sample consisted of sixty cephalometric radiographs of white Brazilian adult patients, with a mean age of 27 years and 6 months, who had not undergone orthodontic treatment and who presented well-balanced faces and normal occlusion. The sample was standardized according to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
(41 reference statements)
3
19
1
Order By: Relevance
“…Another study found that the mean symphysis width of Caucasian Brazilian adults with a well-balanced face and normal occlusion measured from LCR was 15.61 mm, with no significant difference between sexes. 26 Compared with the present findings, the wider symphysis thickness measured in that study might result from LCR image magnification, different ethnic origin, and measuring methodology. They measured the distance from the buccal to the lingual pogonion, whereas the buccal symphysis width in the present study was derived from the perpendicular distance from the buccal pogonion to its counterpart, which might not be the most posterior point of the lingual curvature.…”
Section: Discussioncontrasting
confidence: 89%
“…Another study found that the mean symphysis width of Caucasian Brazilian adults with a well-balanced face and normal occlusion measured from LCR was 15.61 mm, with no significant difference between sexes. 26 Compared with the present findings, the wider symphysis thickness measured in that study might result from LCR image magnification, different ethnic origin, and measuring methodology. They measured the distance from the buccal to the lingual pogonion, whereas the buccal symphysis width in the present study was derived from the perpendicular distance from the buccal pogonion to its counterpart, which might not be the most posterior point of the lingual curvature.…”
Section: Discussioncontrasting
confidence: 89%
“…It has been reported that a greater inclination of the symphysis is associated with an anterior growth direction and that a smaller inclination is often consistent with hyperdivergent patterns. However, Arruda et al 21 (2012) stated that facial type has no correlation with the symphysis inclination. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that orthodontic movements in lingual or labial directions in this area are a cause of gingival recession [ 5 7 ]. Nevertheless, gingival recession is most commonly described in patients with insufficient bone width and bone height on the lingual and/or labial side of the mandibular alveolar bone [ 8 ]. Hence, tooth movement in the mandible is bound to certain anatomical restrictions ( Figure 1 ).…”
Section: Technical Difficultiesmentioning
confidence: 99%
“…Hence, tooth movement in the mandible is bound to certain anatomical restrictions ( Figure 1 ). In case of decreased external bone substance, a risk of crossing these borders emerges which may lead to bone defects, recessions and—in the worst case scenario—tooth/teeth loss with bone loss of the surrounding alveolar ridge [ 8 , 9 ]. Regardless of a possible cause, several methods of reconstruction exist [ 10 ].…”
Section: Technical Difficultiesmentioning
confidence: 99%